Marketing Strategies Implemented by Hotel Industry during COVID-19 in Malaysia - Rajesh Kumar Nair; Ranjith P.V; Siti Hajar Azlan; Daisy Mui Hung Kee; Shazwanie Amat Sazali; Siti Nadiah Rahmat; Shopanadevi Munusamy; Tejashree Ingole (AIBPM Publisher, 2022)
The emergence of a new strain of virus named the Coronavirus or Covid-19 in short has impacted all countries around the globe. In Malaysia, a restricted movement order has been introduced by the government since March 2020 in the hope of suppressing the wild spread of the virus. Thus, any traveling between different states has been put on hold. With this, the tourism industry has been tremendously affected, and the hotel industry is one of them. Consequently, the hotel industry is forced to develop new marketing strategies that would provide a helping hand in sustaining their business. The creative and innovative ideas that resulted from the initiative ranges from offering sweet deal packages revolving around the concept of working from home and staycation offers aside from the surprising involvement in the food delivering industry allowing the general crowd. A study has been conducted revolving around the hotel establishment in Malaysia to provide insights on the marketing strategies implemented by them throughout the pandemic period. This study highlighted the variety of marketing strategies adopted by the establishments.